Pengaruh Pemberian Beberapa Jenis Ekstrak Tanaman Sebagai Zpt Dan Rasio Amelioran Terhadap Pertumbuhan Dan Produksi Padi Varietas Inpari 12 di Lahan Gambut - Yulistia Septari; Nelvia '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to get the kind of plant extracts as a Plant Growth Regulator (PGR) exogenously given and ameliorant ratio that influential as improving rice growth and production in peatlands. This research had been done in peatlands at Tanjung Air Hitam Village, Pelalawan, started from August 2012 until march 2013. This research had been done experimentally using split plot design. The main plot was the plant extract from banana stump (Z1), bamboo shoot (Z2) and the mixture (Z3). The subplots were ameliorant ratio (compost of Oil Palm Empty Fruit Bunch (OPEFB) and dregs}, with three level treatment, that were 4 : 1 {OPEFB compost 5 ton/ha + dregs 1,25 ton/ha), 2 : 1 (OPEFB compost 5 ton/ha + dregs 2,5 ton/ha) and 1 : 1 (OPEFB compost 5 ton/ha + dregs 5 ton/ha). In this research was got 9 combinations with 3 replications. The result showed that giving of plant extracts and ameliorant ratio was nonsignificant for the plant height, maximum tillers, productive tillers, age of harvest, grain per panicle, grain pithy percentage, weight of 1000 grains and also rice production per plot.   Keywords: Ameliorant, PGR, Rice and Peatland